2011
DOI: 10.1039/c1cc13451e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic combinatorial development of a neutral synthetic receptor that binds sulfate with nanomolar affinity in aqueous solution

Abstract: Using dynamic combinatorial disulfide chemistry we have developed a new generation of neutral synthetic receptors for anions, based on a macrobicyclic peptide structure. These receptors show an exceptional affinity and selectivity for sulfate ions in aqueous solution [log K(a) = 8.67 in 41 mol% (67 volume%) acetonitrile in water]. The high affinity depends on a delicate balance between rigidity and flexibility in the structure of the receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 43 publications
(9 reference statements)
1
41
0
4
Order By: Relevance
“…DCL based on the cyclopeptidic structures developed by Kubik and co-workers. 473 Chemical Reviews 454,455 Some of these macrocycles have been found to form complexes with lanthanides. 456 In a similar way, Lisowski, Gregolinśki, and co-workers have described the synthesis of a [6 + 6] macrocycle 458a from the [2 + 2] macrocycle analogue 458b using Cd(II) as the template (Figure 140).…”
Section: Nonclassical Metal Template Effectsmentioning
confidence: 99%
“…DCL based on the cyclopeptidic structures developed by Kubik and co-workers. 473 Chemical Reviews 454,455 Some of these macrocycles have been found to form complexes with lanthanides. 456 In a similar way, Lisowski, Gregolinśki, and co-workers have described the synthesis of a [6 + 6] macrocycle 458a from the [2 + 2] macrocycle analogue 458b using Cd(II) as the template (Figure 140).…”
Section: Nonclassical Metal Template Effectsmentioning
confidence: 99%
“…In aqueousm edia, disulfidee xchange provides an excellent tool for the generationo fd ynamic libraries. [11] This methodology hasr endered some impressive results, with the formation of somer emarkabler eceptors forb iologically relevant structures such as carbohydrates, [12] anions, [13] and DNA G-quadruplexes. [14] In addition, disulfidec hemistry has shown its potential in the formation of complex linked structures such as catenanes [15] and knots.…”
Section: Introductionmentioning
confidence: 99%
“…28 and 29 were expected to exhibit enhanced anion complex formation by increasing receptor pre-organisation. 55 56 Interestingly, the sulfate affinity of 30 (log K = 5.70 in 50% H 2 O-CH 3 OH (v/v)) is not significantly higher than that of 31 (log K = 4.96 in 50% H 2 O-CH 3 OH (v/v)) despite the increased preorganisation that having three linkers affords. ITC data revealed that such behaviour is likely to be due to the switch in the binding enthalpy from exothermic to endothermic upon increasing the number of linkers.…”
Section: Backbone Modified Cyclic Peptidesmentioning
confidence: 94%